Endothelial Dysfunction Old Concepts and New Challenges - Lenasi, Helena (IntechOpen, 2018)
The endothelium enables communication between blood and tissues and is actively involved in cardiovascular homeostasis. Endothelial dysfunction has been recognized as an early step in the development of cardiovascular diseases: respectively, endothelium represents a potential therapeutic niche with multiple targets. The purpose of the book is to point out some recent findings of endothelial physiology and pathophysiology emphasizing various aspects of endothelial dysfunction connected to the body's internal and external environment. While basic features of the endothelium are presented in an introductory chapter, the authors of the following 17 chapters have provided extensive insight into some selected topics of endothelial (dys)function. The book would hopefully be useful for anyone interested in recapitulating endothelial (patho)physiology and expanding knowledge of molecular mechanisms involved in endothelial dysfunction, relevant also for further clinical investigations.